From the Mirror of the Victim: Reconfiguring Moral Guilt - Etxeberria Mauleon, Xabier (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
In this study it is argued that, against its many critics, guilt is an essential category in the ethical area that takes responsibility of the reality of evil. But, at the same time, it is postulated that guilt expresses itself properly only if it is experienced by the guilty person through the mirror of the victim. This is an aspect usually ignored by both its critics and those who advocate it. However, when guilt is perceived under this light, everything is reconfigured: the focus on the wrongdoer’s subjectivity, the guilty feeling, the relationship between the variables of guilt, responsibility and repentance. From the reconsideration resulting from this point of view, guilt experienced with authenticity does justice to the victim and, concomitantly, is a way of healing for the perpetrator.